Long-term survival with favorable cognitive outcome after chemotherapy in primary central nervous system lymphoma - Kowoll, Annika; Pels, Hendrik; Rogowski, Sabine; Fliessbach, Klaus; Glasmacher, Axel; Engert, Andreas; Reiser, Marcel; Diehl, Volker; Vogt-Schaden, Maria-Elisabeth; Egerer, Gerlinde; Schackert, Gabriele; Reichmann, Heinz; et al. (Annals of neurology, 2010)
Objective To evaluate long-term progression-free survival and overall survival, quality of life, and cognitive function in primary central nervous system lymphoma after systemic and intraventricular chemotherapy without radiotherapy. Methods A long-term follow-up was conducted on surviving primary central nervous system lymphoma patients having been enrolled in a pilot/phase II trial between September 1995 and December 2001. Initially, 65 patients (median age, 62 years) had been treated with systemic and intraventricular chemotherapy without radiotherapy. All living patients were contacted, and a neurological examination, comprehensive neuropsychological testing, quality-of-life assessment, and imaging were performed. Results Twenty-one of all 65 patients (32 %) and 17 of 30 patients 60 years or younger (57%), respectively, were still alive at median follow-up of 100 months (range, 77-149 months). Nineteen of 21 patients completed all investigations; 1 was lost to follow-up. In three patients, an exclusively extraneural relapse of a high-grade non-Hodgkin's lymphoma was diagnosed after 9, 31, and 40 months, respectively. All of them experienced complete remission to high dose. Neither late neurotoxicity nor compromise of quality of life was found in any of the patients examined. Interpretation Primary polychemotherapy based on high-dose methotrexate (MTX) and cytarabine (Ara-C) is highly efficient in treatment of primary central nervous system lymphoma. About half of patients 60 years or younger can obviously be cured with this regimen without long-term neurotoxic sequelae or quality-of-life compromise. ANN NEUROL 2010;67:182-189